Information Representation and the Role of e-News Media on Bullying Cases of Students with Learning Difficulties at School - Nuning Kurniasih; Savitri Wanabuliandari; Ristiyani Ristiyani (EDUTEC : Journal of Education And Technology, 2025)
This study aims to see how the information representation and the role of e-news media on bullying cases of students with learning difficulties or called slow learners in e-news media. This research uses qualitative research through content analysis. The object of the research is e-news about bullying cases by two teachers in a school in Medan and bullying cases by several students in a school in Semarang, on detik.com and kompas.com. The results showed that the representation of information about bullying on students with learning difficulties in schools included information about the beginning of viral cases on social media, personal experiences, negative impact on victims of bullying, the results of investigations of various related parties, consequences for perpetrators of bullying, information containing support for victims of bullying, policies and programs to prevent bullying, information containing education for the public, information in order to build awareness and solidarity and action of the anti-bullying movement. These representations of information illustrate that e-news media do not only present news in the sense of reporting a case, but also support information literacy by providing understanding, concern and awareness of bullying cases. Meanwhile, e-news media have played a role in disseminating information, conducting anti-bullying campaigns, creating an open culture in discussing cases of bullying in the public sphere, providing education, building public awareness and solidarity in bullying prevention actions, providing advocacy, intervention and collecting feedback from the public on policies and implementation of the anti-bullying movement. In the end, e-news media is expected to be able to participate in the bullying prevention movement in schools.